Peran Orang Tua Dalam Mendampingi Pembelajaran Daring Saat Pandemi Covid-19 di MI Al-Hidayah - Wahyu Ningsih; Resma Anisa Fitri; Mamal Maulana (Jurnal Dirosah Islamiyah, 2022)
The Covid-19 pandemic has made various changes in every aspect of life, one of which is education. This study aims to find various obstacles and describe the role of people parents when accompanying or giving direction to their children in learning at home. Use the method in this research is the description method. Furthermore, the data collection techniques used. The techniques used are interview, observation, listening, and note-taking techniques. The results of this study show various obstacles for parents in online learning including, internet signals that sometimes difficult, expensive qoutas, parents are less able to guide and fully understand the material, so it can’t be maximal in teaching children, there is no cellphone, so it is necessary to ask questions directly to his friends. The participation of parents is very supportive of the succcess of the achievment child. Always motive and provide innovations in guiding chilren, so that children do not bored and even stressed in learning, there must be good coordination between parents and teachers. Evaluation is needed in order to improved student achievement result Keywords: Obstachles, The role of Parents Covid-19 Pandemic